Magnetic Resonance Angiography of the Thoracic Vasculature: Technique and Applications. Issue 2 (14th February 2020) - Ludwig, Daniel R.; Shetty, Anup S.; Broncano, Jordi; Bhalla, Sanjeev; Raptis, Constantine A.
Abstract : Magnetic resonance angiography (MRA) is a powerful clinical tool for evaluation of the thoracic vasculature. MRA can be performed on nearly any magnetic resonance imaging (MRI) scanner, and provides images of high diagnostic quality without the use of ionizing radiation. While computed tomographic angiography (CTA) is preferred in the evaluation of hemodynamically unstable patients, MRA represents an important tool for evaluation of the thoracic vasculature in stable patients. Contrast‐enhanced MRA is generally performed unless there is a specific contraindication, as it shortens the duration of the exam and provides images of higher diagnostic quality than noncontrast MRA. However, intravenous contrast is often not required to obtain a diagnostic evaluation for most clinical indications. Indeed, a variety of noncontrast MRA techniques are used for thoracic imaging, often in conjunction with contrast‐enhanced MRA, each of which has a differing degree of reliance on flowing blood to produce the desired vascular signal. In this article we review contrast‐enhanced MRA, with a focus on contrast agents, methods of bolus timing, and considerations in imaging acquisition. Next, we cover the mechanism of contrast, strengths, and weaknesses of various noncontrast MRA techniques. Finally, we present an approach to protocol development and review representative protocols used at our institution for a variety of thoracic applications. Further attention will be devoted to additional techniques employed to address specific clinical questions, such as delayed contrast‐enhanced imaging, provocative maneuvers, electrocardiogram and respiratory gating, and phase‐contrast imaging. The purpose of this article is to review basic techniques and methodology in thoracic MRA, discuss an approach to protocol development, and illustrate commonly encountered pathology on thoracic MRA examinations. Level of Evidence : 5 Technical Efficacy Stage : 3